2020
DOI: 10.1080/15476286.2020.1812894
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP1 is a targetable SRC/MAPK-dependent driver of invasive growth in ovarian cancer

Abstract: Epithelial-to-mesenchymal transition (EMT) is a hallmark of aggressive, mesenchymal-like high-grade serous ovarian carcinoma (HGSOC). The SRC kinase is a key driver of cancer-associated EMT promoting adherens junction (AJ) disassembly by phosphorylation-driven internalization and degradation of AJ proteins. Here, we show that the IGF2 mRNA-binding protein 1 (IGF2BP1) is up-regulated in mesenchymal-like HGSOC and promotes SRC activation by a previously unknown protein-ligand-induced, but RNA-independent mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Nonetheless, all three IGF2BPs are highly expressed and function as independent prognostic factors in a variety of cancers, including lung cancer 89 , 90 , liver cancer 91 - 93 , breast cancer 94 , 95 , colorectal cancer 96 - 98 , pancreatic cancer 99 - 101 , prostate cancer 102 , bladder cancer 103 - 105 , thyroid cancer 106 - 108 , gastric cancer 109 , 110 , renal cell carcinoma 111 , ovarian cancer 112 , 113 , esophageal squamous cell carcinoma 114 , 115 , acute myeloid leukemia 116 . In addition to the high expression of the IGF2BPs itself, intercellular communication factors, such as tumor-secreted extracellular vesicles (EVs), can maintain the stability of IGF2BPs in cells to promote the development of cancer.…”
Section: The Oncogenic Role Of Igf2bps In Cancermentioning
confidence: 99%
“…Nonetheless, all three IGF2BPs are highly expressed and function as independent prognostic factors in a variety of cancers, including lung cancer 89 , 90 , liver cancer 91 - 93 , breast cancer 94 , 95 , colorectal cancer 96 - 98 , pancreatic cancer 99 - 101 , prostate cancer 102 , bladder cancer 103 - 105 , thyroid cancer 106 - 108 , gastric cancer 109 , 110 , renal cell carcinoma 111 , ovarian cancer 112 , 113 , esophageal squamous cell carcinoma 114 , 115 , acute myeloid leukemia 116 . In addition to the high expression of the IGF2BPs itself, intercellular communication factors, such as tumor-secreted extracellular vesicles (EVs), can maintain the stability of IGF2BPs in cells to promote the development of cancer.…”
Section: The Oncogenic Role Of Igf2bps In Cancermentioning
confidence: 99%
“…RNA-sequencing, qRT-PCR or Western blotting was performed 96 h (PANC-1) or 72 h (all other cell lines) post transfection referring to approximately three doublings. For RNA decay analyses, cells were treated with Actinomycin D (5 μM, Sigma Aldrich) for indicated time points 72 h upon transfection.mRNA levels were quantified by QRT-PCR based on the SYBRGreenI ® technology as previously described (Bley et al, 2020). Western blotting using the LI-COR Odyssey infrared scanning system for detection was performed as previously described in detail (Bley et al, 2020).…”
Section: Cell Culture Transfection Qrt-pcr and Western Blottingmentioning
confidence: 99%
“…For example, Gu et al (2004) showed that increased IGF2BP1 expression is associated with an advanced clinical stage and poor prognosis in patients with OC. As shown in the study by Bley et al (2021) , IGF2BP1 is a targetable SRC/MAPK-dependent driver of invasive growth in OC. In addition, Qin et al (2017) reported that the restoration of miR-708 sensitizes OC cells to cisplatin via the IGF2BP1/Akt pathway.…”
Section: Discussionmentioning
confidence: 79%